HUBUNGAN FAKTOR DEMOGRAFI DENGAN MOTIVASI MENJADI GURU SEBAGAI PILIHAN KARIR : SELF-REPORTED SURVEY - Ahmad Kamal Sudrajat; Risma Wiharyanti; Fera Aulia; Dita Purwinda Anggrella (JURNAL TARBIYAH, 2022)
Motivation to become a teacher is important information to be used in preservice teacher education programs. The purpose of this study was to determine the relationship between demographic factors and motivation to choose teachers as career choices in teacher education students. The type of research used in this research is survey. The research subjects were students of the second year at the Department of Biology Education, Universitas Negeri Yogyakarta. The results showed that hometown of students had a relationship with motivation to become a teacher, students from city areas had higher scores. The results of the analysis on each aspect indicate that hometown of students has a relationship with the aspect of job security (Sig = 0.036) and gender has a relationship with the aspect of work with children and adolescents (Sig = 0.042). In addition, gender and hometown of students have a relationship with aspects of enhancing social equality (Sig = 0.015; Sig = 0.021). The conclusion in this study is that the student's hometown has a relationship with their motivation to become a teacher as a career choice, while gender and family background have no relationship.